ANALITICAL METHOD VALIDATION OF ANIONIC SURFACTANT SODIUM DODECYL BENZENE SULFONATE (SDBS) IN CATFISH BY UV-VIS SPECTROPHOTOMETRY USING ACRIDINE ORANGE - Monica Cahyaning Ratri; Adhitasari Suratman; Roto Roto (ALCHEMY Jurnal Penelitian Kimia, 2017)
The analytical method development on an anionic surfactant of sodium dodecylbenzenesulfonate (SDBS) in a catfish using spectrophotometer UV-Vis using acridine orange (AO) has been conducted. This research aims to determine the optimum conditions of analysis and to determine validation parameters of sodium dodecylbenzenesulfonate (SDBS) analysis in a catfish. This study was divided into two steps, isolation of sodium dodecyl benzene sulfonate (SDBS) in the catfish with soxhlet extraction and the analysis of SDBS. The analysis of sodium dodecylbenzenesulfonate (SDBS) is based on the formation of ion pair between dodecylbenzenesulfonate (DBS) and acridine orange (AO). The results showed that the analysis can be performed at 499 nm, using ethanol as acridine orange (AO) solvent, the mole ratio of dodecylbenzenesulfonate (DBS) acridine orange (AO) 2:1, and pH 2.97. The parameters of validation had good acceptability as linearity (r) 0.998, limit of detection 0.0343 mg/L   and limit of quantification 0.104 mg/L, precision 0.382 - 1.78 %, sensitivity 4.64 x 104 L mol-1cm-1, and accuracy (82.11 - 100.3 %).